Analysis of a development program for the existing Bangkok International Airport - Arunrojana, Kosol 1948- (1980)
An Airport as an obvious stimulus to society from the standpoint of economic growth and the services it offers to then public is a big contributing factor to the progress of a country. At this present age of all the latest things in life and war, it is unimaginable for a country without an International Airport. It can be said that a country without an International Airport is living in the era when man does not know the meaning of fashion, music, activism and gasoline. Thailand, - a Kingdom - a country in Southeast Asia is with an International Airport existing up to the present without a complete master plan. It had existed the odds of time yet surviving the demands of aviation. As an Airport complex both for military and commercial use, it had served the international and domestic air transportation problems of Thailand. However, comes a time even to a man's life and habits that there must be a change. Culture changes to cope up with the advancing generation. Arts and sciences, individual and society, labor and industry, trade and technology all advance with the time. Because man can not settle for every material possession he has, can not content with what is on hand. Time make things obsolete, and the modern age had made some of the aviation needs at BIA obselete. With this as the consideration, there is a need to have a new master plan for the existing BIA. With the changes the new development plan will give to the BIA it is expected that what the country gained before will have a hundred fold profit in international affairs. The Airport as the door of inbound and outbound communication with the international world is surely to bring to the country the latest in everything. A development plan is needed.